Pengaruh Lingkungan Kerja dan Work Life Balance Terhadap Stres Kerja pada Hotel X - Luh Esta Yanti; Ida Bagus Koman Suarmaja (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the simultaneous and partial effects of the work environment and work-life balance on employee work stress at Hotel X. The research design is causal quantitative, with multiple linear regression analysis using SPSS 26.0 for Windows. The sample was obtained through purposive sampling (non-probability) of 120 respondents. The research subjects were employees working in shifts. The analysis results show that, (1) both variables simultaneously have a negative and significant effect on work stress, (2) the work environment has a negative and significant effect (sig. 0.002), and (3) work-life balance has a negative and significant effect (sig. 0.000). The work-life balance variable dominates its influence compared to the work environment, as seen from the lower significance value. These findings confirm that improving work-life balance and the work environment effectively reduces stress, especially for shift workers who are vulnerable to time imbalance. Based on the results, organizations are advised to optimize human resource management by maintaining a balance between job demands and employee conditions, as well as ensuring a proportional workload. Improvement in work-life balance can be achieved through flexible leave policies, adequate breaks between shifts, no overtime days except in emergencies, and minimizing personal time interruptions. These steps are expected to enhance employee well-being, retention, and productivity in the hospitality sector. Further research is recommended to explore different variables and methods, including comparing non-shift employees with the same variables, for more comprehensive insights.